RANCANG BANGUN ANTARMUKA WEB RESPONSIF UNTUK SISTEM PEMBELAJARAN MANDIRI DENGAN HTML5 - , PUTRA; , Dr. Ridi Ferdiana, S.T., M.T ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Requirement of concept and learning mechanism (education) based IT (e-learning) becomes inevitable. The concept of system self-learning have make impact in transformation process of education conventional into digital form, either on contents or in system. System self-learning itself is usually shaped website, when we can access with internet. The employing of different device in Indonesian become spotlight for to design of website system self-learning when we can access in different type of device. The user interface design for each devices must meet the requirements so that any user can experience and access the service in the most user-friendly manner. In kind of the user interface design, the first phase is should to begin with make a sketch of website. The next phase is a making of the user interface with HTML5 code. Furthermore is to add framework bootstrap so as to the display of website will look the well and responsive. The product of this research is a website system self-learning which can be access in different device like PC desktop (kind of web browser), Tablet PC (based Android and iOS) and smartphone (based android, iOS, Windows Phone and Blackberry). The display of website can adjust itself with width screen device, commonly known as responsive web design techniques.